2021
DOI: 10.3390/medicina58010054
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Free Flap Reconstruction of a Complex Intraoral Defect after Squamous Cell Carcinoma Excision: A Case Report

Abstract: Background: Squamous cell carcinoma is the most frequent malignant cancer of the oral cavity. Metastasis involvement is one of the most relevant prognostic factors in terms of survival probability. Patients with oral cancers often undergo extensive en bloc resective surgery of the mandible and maxilla, with or without cervical nodal dissection, based on the presence or occult risk of regional metastases. Several factors affect the choice of flap, to recover aesthetics and function. Case Presentation: The case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Consequently, the combination of multiple flaps has emerged as an innovative therapeutic approach (Lee et al, 2010;Weitz et al, 2015;Hsieh and Bewley, 2019;Silva et al, 2019;Moratin et al, 2021;Raghuram et al, 2021;Santilli et al, 2021;Tharakan et al, 2023). The ALT can furnish sufficient tissue volume and can be fashioned into a chimeric flap with minimal impact on the donor site, rendering it an Frontiers in Bioengineering and Biotechnology frontiersin.org optimal choice for repair and reconstruction of large soft tissue defects in the oromandibular region (Thomas et al, 2020).…”
Section: Case Presentationmentioning
confidence: 99%
“…Consequently, the combination of multiple flaps has emerged as an innovative therapeutic approach (Lee et al, 2010;Weitz et al, 2015;Hsieh and Bewley, 2019;Silva et al, 2019;Moratin et al, 2021;Raghuram et al, 2021;Santilli et al, 2021;Tharakan et al, 2023). The ALT can furnish sufficient tissue volume and can be fashioned into a chimeric flap with minimal impact on the donor site, rendering it an Frontiers in Bioengineering and Biotechnology frontiersin.org optimal choice for repair and reconstruction of large soft tissue defects in the oromandibular region (Thomas et al, 2020).…”
Section: Case Presentationmentioning
confidence: 99%
“…Studies have shown that surgical management is one of the primary treatment modalities necessary for achieving optimal survival outcomes in patients with oral cancer [ 2 , 3 ]. The principal surgical treatment for advanced oral cancer is en bloc cancer resection; however, thorough resection leaves a significant defect that has a substantial impact on the intricate structures and functions of the oral and maxillofacial areas [ 4 , 5 ]. Moreover, extensive resection might cause malformation, disfigurement, and dysfunction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%